2013
DOI: 10.1155/2013/218627
|View full text |Cite
|
Sign up to set email alerts
|

The Antinociceptive and Anti‐Inflammatory Activities of Aspidosperma tomentosum (Apocynaceae)

Abstract: We investigated the antinociceptive and anti-inflammatory activities of the crude ethanolic extract (CEE), its fractions, and the flavonoid isorhamnetin from Aspidosperma tomentosum using models of nociception and inflammation in mice. In the writhing test, the CEE and its fractions (except for soluble phase, CHCl3 100% and EtAcO 100%) at 100 mg/kg p.o. induced antinociceptive activity. Isorhamnetin (100 μmol/kg, p.o.) was also active. In the hot plate test, only the treatment with the fractions Hex : CHCl3 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…10 With the purpose of identifying plants ant natural products with pharmacological activities, our research group performed previous ethnopharmacological studies with many plants with antinociceptive and antiinflammatory activities. [11][12][13] Thus, the major aim of the current study was to evaluate the ethanol extract, fractions and one pure compound, an epicatechin derivative obtained from the stem bark of X. americana, for their antinociceptive and antiinflammatory activities. In vitro models were used to help in the assessment of their medicinal properties, supporting the ethnopharmacological use of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…10 With the purpose of identifying plants ant natural products with pharmacological activities, our research group performed previous ethnopharmacological studies with many plants with antinociceptive and antiinflammatory activities. [11][12][13] Thus, the major aim of the current study was to evaluate the ethanol extract, fractions and one pure compound, an epicatechin derivative obtained from the stem bark of X. americana, for their antinociceptive and antiinflammatory activities. In vitro models were used to help in the assessment of their medicinal properties, supporting the ethnopharmacological use of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…The intraperitoneal administration of agents that irritate serous membranes provokes a stereotyped behaviour in the mice which is characterized by abdominal contractions, movements of the body as a whole and twisting of the dorso-abdominal muscles [22] and a reduction in motor activity and motor incoordination [23]. It has been suggested that acetic acid injection into peritoneal cavity leads to increased levels of cyclooxygenases (COX) and lipoxygenase [24] and indirectly leads to the release of endogenous nociceptive mediators such as PGE 2 and PGF 2α [5,20,[25][26][27][28][29][30], serotonin [22,25,26,29,30], histamine [22,26,30,31], bradykinin [21,22,24], substance P [24,25], cytokines (TNF-α, IL-1β, IL-8) [21,24,25,29] and lipoxygenase products [20], which eventually excites the primary afferent nociceptors [25] that contribute to the development of inflammatory pain [22]. The data presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified in A. pyrifolium insecticidal [90], antibacterial [91] and hypotensive activities [92]. Another plant studied by our group was A. tomentosum, which showed great anti-hipertensive [93,94], antinociceptive, anti-inflammatory and analgesic [95][96][97][98] and A. macrocarpum, which showed anti-hypertensive activity in spontaneously hypertensive mice [99].…”
Section: Phytochemicals -Isolation Characterisation and Role In Humamentioning
confidence: 99%